The convergence of factors that affect the dairy product market: A comparative analysis of European Union countries - Jurij Klapkiv; Petro Putsenteilo; Vitalii Karpenko (Comparative Economic Research. Central and Eastern Europe, 2023)
The European Union is a large producer of milk and dairy products. It is also a significant market for the consumption of dairy products, which is characterised by effective demand, and it significantly influences the markets of other food products. The main milk producers in the EU are Germany, France, Poland, the Netherlands, Italy and Spain. Intensive migration has contributed to additional demand for food products, in particular, dairy products. This provided the basis for the construction and calculation of a dynamic model of dairy production, the export of dairy products, and the coexistence with the existing population as the main consumers in the EU-27 countries and Great Britain between 2004 and 2020. An additional research value is that based on the presentation of the analysis and modeling, the relationship between the growth in the demand for dairy products and the growth in the population is established. The reason for the large population in the countries of Central and Eastern Europe is intensive migration flows, which increase the demand for dairy products. The increase in volumes reduces the cost price, which contributes to the export of dairy products, and also contributes to the increase in the volume of production of dairy products. The resulting models made it possible to analyse the influence of population growth on the increase in production volume. At the same time, the dependence and influence of the export of dairy products on the increase in the volume of production of dairy products in the EU-27 and Great Britain countries is investigated. The results of the mathematical modelling indicate unique opportunities to develop the dairy sector of individual EU-27 countries, i.e., the Czech Republic, the Netherlands, and Poland. These countries have a rational ratio of the influence of the population growth factor on the increase in the volume of dairy production and the optimal influence of the export of dairy products on the increase in the volume of dairy production.
Keywords: F10; J11; Q11; Q17; 330; milk; dairy products; European Union; milk producers; consumers; export of dairy products; cost; price; profitabilit